Road surface frozen prevention method

JP2025041263AActive Publication Date: 2025-03-26MAEDA ROAD CONSTR CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023148454
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-26
Estimated Expiration
2043-09-13

Smart Images

  • Figure 2025041263000001
    Figure 2025041263000001
  • Figure 2025041263000002
    Figure 2025041263000002
  • Figure 2025041263000003
    Figure 2025041263000003
Patent Text Reader

Abstract

To provide a road surface frozen prevention method, which can be easily implemented, and can enhance and sustain frozen prevention effect.SOLUTION: A road surface frozen prevention method includes a first process to disperse on road surface antifreeze agent containing a metal salt compound of an organic acid, and a second process to apply mortar containing polymer emulsion, solidifying agent, and an aggregates on the road surface to form a mortar layer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for suppressing freezing of road surfaces such as road pavements. [Background technology]

[0002] In snowy and cold regions, the use of studded tires has been prohibited in a wider range of areas, and studless tires have become the mainstream winter tires, causing problems with reduced skid resistance on snowy and icy roads. For this reason, preventing roads from freezing in winter has become an important issue from the perspective of traffic safety.

[0003] As a method for suppressing the freezing of such road surfaces, for example, Patent Document 1 discloses a method of spraying a freeze-inhibiting surface treatment mixture containing a metal salt compound of an organic acid, a polymer emulsion, a solidifying agent, and an aggregate onto the road surface. However, the freeze-inhibiting surface treatment mixture has a short pot life, so that the spraying machine is prone to clogging. In addition, the freeze-inhibiting surface treatment mixture has a long hardening time, so it may be necessary to heat the mixture using a burner or the like after spraying it onto the road surface. In addition, in the case of application by spraying, a great deal of effort is required to cure the work area in order to prevent contamination by scattered materials. Thus, the method using the freeze-inhibiting surface treatment mixture of Patent Document 1 had the problem that application was difficult due to the above factors. In addition, there was a demand for further improvement in the freeze-inhibiting effect and the durability of the freeze-inhibiting effect. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-76210 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been proposed in consideration of the above, and aims to provide a method for preventing road surface freezing that can be easily applied and can enhance the anti-freezing effect and the durability of the anti-freezing effect. [Means for solving the problem]

[0006] As a result of intensive research into solving the above-mentioned problems, the inventors discovered that the above-mentioned problems can be solved by a road surface anti-freezing method comprising a first step of spraying a road surface with an anti-freezing agent containing a metal salt compound of an organic acid, and a second step of applying a mortar containing a polymer emulsion, a solidifying agent, and an aggregate to the road surface, and thus completed the present invention.

[0007] [1] According to aspect 1 of the present invention, there is provided a method for suppressing freezing of road surfaces, comprising: a first step of spraying a freezing inhibitor containing a metal salt compound of an organic acid onto a road surface; and a second step of applying mortar containing a polymer emulsion, a solidifying agent, and an aggregate onto the road surface.

[0008] [2] According to a second aspect of the present invention, there is provided the method for suppressing freezing of road surfaces as recited in the first aspect, wherein the content of the metal salt compound of an organic acid in the antifreeze agent is 5 to 45% by weight.

[0009] [3] According to the third aspect of the present invention, in the first step, the amount of the antifreeze agent sprayed is 0.05 to 0.5 L / m 2 The method for suppressing road surface freezing according to embodiment 1 or 2 is provided, wherein

[0010] [4] According to the fourth aspect of the present invention, in the first step, the amount of the metal salt compound of the organic acid placed on the road surface by spraying the antifreeze agent is 2.5 to 225 g / m 2 There is provided a method for suppressing road surface freezing according to any one of Aspects 1 to 3, wherein

[0011] [5] According to a fifth aspect of the present invention, there is provided the method for suppressing freezing of road surfaces according to any one of the first to fourth aspects, wherein in the second step, the mortar layer has a thickness of 0.2 to 4 mm.

[0012] [6] According to a sixth aspect of the present invention, there is provided a method for suppressing freezing of road surfaces according to any one of the first to fifth aspects, wherein the second step is carried out 10 minutes to 2 hours after the first step.

[0013] [7] According to a seventh aspect of the present invention, there is provided the method for suppressing icing of road surfaces according to any one of the first to sixth aspects, wherein the metal salt compound of an organic acid is a metal salt of a carboxylic acid.

[0014] [8] According to an eighth aspect of the present invention, there is provided the method for suppressing freezing of road surfaces according to the seventh aspect, wherein the metal salt compound of an organic acid is a metal salt of formic acid.

[0015] [9] According to a ninth aspect of the present invention, there is provided the method for suppressing freezing of road surfaces according to any one of the first to eighth aspects, wherein the polymer emulsion is an emulsion of an acrylic ester polymer. Effect of the Invention

[0016] According to the present invention, a method for suppressing freezing on road surfaces can be provided which can be easily carried out and which can improve the anti-freezing effect and the durability of the anti-freezing effect. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a diagram for explaining the ice adhesion tensile test method. [Diagram 2] FIG. 2 is a graph showing the results of the ice adhesion tensile test. [Diagram 3] FIG. 3 is a graph showing the results of the ice adhesion tensile test after the application of snow-melting agent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The road surface anti-freezing method in this embodiment includes a first step of spraying an anti-freezing agent containing a metal salt compound of an organic acid on a road surface, and a second step of applying mortar containing a polymer emulsion, a solidifying agent, and an aggregate to the road surface. According to the road surface anti-freezing method in this embodiment, a mortar layer made of mortar containing a polymer emulsion, a solidifying agent, and an aggregate is formed on the road surface on which the anti-freezing agent has been sprayed. This makes it possible to impart an anti-freezing effect to road surfaces such as paved roads.

[0019] In the first step, a freeze inhibitor containing a metal salt compound of an organic acid is sprayed on the road surface. The freeze inhibitor is an aqueous solution containing a metal salt compound of an organic acid. The method of spraying the freeze inhibitor on the road surface is not particularly limited, but for example, a method of pumping the freeze inhibitor stored in a tank and spraying it on the work area using a sprayer can be mentioned. In addition, although not particularly limited, in order to fully exert the freeze inhibitor effect of the present invention, it is preferable to clean the road surface with a blower or the like before the first step.

[0020] The metal salt compound of an organic acid is a compound that exhibits a freeze-suppressing effect due to a freezing point lowering action. Such a metal salt compound of an organic acid is not particularly limited as long as it is a metal salt of an organic acid, but examples thereof include metal salts of carboxylic acids and metal salts of sulfonic acids, and from the viewpoint of further enhancing the freeze-suppressing effect, metal salts of carboxylic acids are preferred. In addition, the carboxylic acid is not particularly limited, and examples thereof include saturated aliphatic monocarboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, and caproic acid; saturated aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, and maleic acid; hydroxycarboxylic acids such as lactic acid, malic acid, and citric acid; unsaturated aliphatic monocarboxylic acids such as acrylic acid, methacrylic acid, oleic acid, and linoleic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, and terephthalic acid; and the like. Among these, from the viewpoint of a high freeze-suppressing effect, saturated aliphatic monocarboxylic acids are preferred, formic acid, acetic acid, and propionic acid are more preferred, and formic acid is particularly preferred.

[0021] In addition, the metal constituting the metal salt compound of an organic acid is not particularly limited, but examples include metals in Group 1 of the periodic table, such as lithium, sodium, potassium, rubidium, and cesium, and metals in Group 2 of the periodic table, such as beryllium, magnesium, calcium, strontium, and barium. Among these, from the viewpoint of further enhancing the anti-freezing effect, metals in Group 1 of the periodic table are preferred, with lithium, sodium, and potassium being more preferred, and sodium being particularly preferred.

[0022] The content of the metal salt compound of an organic acid in the freeze inhibitor is preferably 5 to 45% by weight, more preferably 10 to 35% by weight, and even more preferably 15 to 25% by weight. By setting the content of the metal salt compound of an organic acid in the freeze inhibitor within the above range, the freeze inhibitor effect can be further improved.

[0023] The amount of antifreeze agent to be sprayed in the first step is preferably 0.05 to 0.5 L / m per unit area of ​​the road surface. 2 , more preferably 0.08 to 0.4 L / m 2 , and more preferably 0.1 to 0.3 L / m 2 It is.

[0024] The amount of the metal salt compound of an organic acid placed on the road surface in the first step is preferably 2.5 to 225 g / m2 per unit area of ​​the road surface. 2 and more preferably 8 to 140 g / m 2 and more preferably 15 to 75 g / m 2 By setting the amount of the metal salt compound of an organic acid sprayed on the road surface within the above range, the anti-freezing effect can be further improved. The amount of the metal salt compound of an organic acid placed on the road surface can be adjusted by adjusting the content of the metal salt compound of an organic acid in the anti-freezing agent and the spray amount of the anti-freezing agent.

[0025] In the second step, mortar containing a polymer emulsion, a solidifying agent, and an aggregate (polymer cement mortar) is applied onto the road surface onto which the antifreeze agent has been sprayed.

[0026] The polymer emulsion contained in the mortar is not particularly limited as long as it is a polymer dispersion in which a polymer is dispersed in water, and examples of the polymer emulsion include an acrylic polymer emulsion, a vinyl acetate polymer emulsion, a butadiene polymer emulsion, and a natural rubber emulsion.

[0027] Specific examples of acrylic polymer emulsions include emulsions of (meth)acrylic acid ester polymers obtained by polymerizing (meth)acrylic acid esters (meaning acrylic acid esters and / or methacrylic acid esters), and emulsions of (meth)acrylic acid ester-butadiene copolymers obtained by copolymerizing (meth)acrylic acid esters and butadiene.

[0028] Specific examples of emulsions of vinyl acetate polymers include emulsions of ethylene-vinyl acetate copolymers (EVA) and emulsions of polyvinyl acetate (PVAC).

[0029] Specific examples of the butadiene polymer emulsion include an emulsion of a styrene-butadiene copolymer obtained by copolymerizing styrene and butadiene, and an emulsion of an acrylonitrile-butadiene copolymer obtained by copolymerizing acrylonitrile and butadiene.

[0030] Among the above-mentioned polymer emulsions, from the viewpoint of being able to further enhance the durability of the anti-freezing effect, emulsions of acrylic polymers are preferred, and emulsions of acrylic ester polymers obtained by polymerizing acrylic esters are more preferred.

[0031] The glass transition temperature (Tg) of the polymer contained in the polymer emulsion is preferably less than 0° C., more preferably −10° C. or lower, and particularly preferably −20° C. or lower, from the viewpoint of further enhancing the durability of the freeze suppression effect.

[0032] Furthermore, the proportion of the polymer in the polymer emulsion (proportion of solids) is not particularly limited, but is preferably 20 to 70 mass %, more preferably 30 to 50 mass %, and even more preferably 35 to 45 mass %.

[0033] The content of polymer emulsion in mortar is the amount per 100 parts by weight of aggregate. The content is preferably 20 to 70 parts by weight, more preferably 30 to 50 parts by weight, and further preferably 35 to 45 parts by weight. By setting the content of the polymer emulsion within the above range, the durability of the anti-freezing effect can be further increased.

[0034] The solidification material contained in the mortar may be any material capable of reacting with the water contained in the polymer emulsion to harden, and for example, cement can be suitably used. The cement is not particularly limited, and examples thereof include Portland cements such as ultra-fast hardening cement, ultra-high-early strength Portland cement, high-early strength Portland cement, and ordinary Portland cement, mixed cements such as blast furnace cement and fly ash cement, and ecocement. Among these, from the viewpoint of early traffic opening, ultra-fast hardening cement, ultra-high-early strength Portland cement, and high-early strength Portland cement are preferred, and ultra-fast hardening cement is more preferred.

[0035] The content of the solidifying agent in the mortar is preferably 20 to 60 parts by weight, more preferably 30 to 50 parts by weight, and further preferably 35 to 45 parts by weight, based on 100 parts by weight of the aggregate.

[0036] The aggregate contained in the mortar is not particularly limited, and crushed stone, sand, stone powder, and other aggregates that are used for normal road paving can be appropriately used, but from the viewpoint of improving the applicability of the road surface freeze-inhibiting surface treatment mixture of the present invention when applied to road surfaces such as paved roads, fine aggregates such as silica sand (quartz sand), river sand, mountain sand, land sand, sea sand, crushed sand, and the like are preferred. In addition, the aggregate is preferably one in which the proportion of aggregates having a grain size of 0.6 mm or less in the total amount of aggregate is 0 to 50 mass%, and more preferably one in which the proportion of aggregates having a grain size of 0.6 mm or less is 10 to 30 mass%.

[0037] In addition to the above, the mortar may contain additives that are commonly used in paved road surfaces, such as hardening accelerators, fluidizing agents, defoamers, retarders, fillers, vegetable fibers, pigments, etc., so long as the effects of the present invention are not impaired. Mortar can be produced by mixing the above components.

[0038] The method for applying mortar to the road surface is not particularly limited, but examples include a method in which mortar mixed with a hand mixer or the like is placed within the work area and then spread evenly using a rubber rake or a method in which mortar is applied and spread evenly using a vehicle equipped with a mixing device and / or a spreader box.

[0039] The thickness of the mortar layer formed in the second step is preferably 0.2 to 4 mm, more preferably 0.5 to 3 mm, and further preferably 1 to 2 mm. The thickness of the mortar layer can be adjusted by adjusting the blending ratio of each component contained in the mortar, or by spreading the mortar evenly to a desired thickness when applying the mortar.

[0040] The thickness of the mortar layer formed in the second step is not particularly limited, but is preferably 0.0008 to 1.6 mm / (g / m) in terms of the thickness relative to the amount of the metal salt compound of an organic acid placed on the road surface per unit area in the first step. 2 ), and preferably 0.003 to 0.38 mm / (g / m 2), and more preferably 0.01 to 0.14 mm / (g / m 2 By setting the thickness of the mortar layer relative to the amount of the metal salt compound of an organic acid within the above range, the freeze-inhibiting effect of the freeze-inhibiting agent and the durability of the freeze-inhibiting effect can be further improved.

[0041] Although not particularly limited, the second step is preferably carried out 10 minutes to 2 hours, more preferably 30 minutes to 1 hour after the first step. By carrying out the second step a predetermined time after the first step, the mortar can be appropriately hardened, and the freeze-inhibiting effect of the freeze-inhibiting agent and the durability of the freeze-inhibiting effect can be further increased.

[0042] In the second step, after the mortar is applied, it is preferable to cure the mortar as necessary to harden the mortar.

[0043] In the road surface antifreeze method of this embodiment, in the first step, an antifreeze agent containing a metal salt compound of an organic acid is sprayed on the road surface, and then in the second step, mortar containing a polymer emulsion, a solidifying agent, and an aggregate is applied. This allows the balance between the pot life and hardening time of the mortar to be appropriately adjusted using a mortar with a desired composition, making it easy to handle the mortar and enabling simple construction.

[0044] In addition, in this embodiment, by forming a mortar layer on the antifreeze agent spread on the road surface, the durability of the antifreeze effect of the antifreeze agent can be improved. Although the reason for this is unclear, it is thought that the mortar layer acts as a sealing layer, improving the sustained release of the metal salt compound of the organic acid contained in the antifreeze agent.

[0045] In addition, the mortar layer formed using the above mortar has fine voids on the surface and inside. Therefore, the antifreeze agent sprayed in the first step can seep out from the voids in the mortar layer formed in the second step to the surface of the mortar layer. Therefore, according to the road surface antifreeze method of this embodiment, the antifreeze effect of the antifreeze agent can be effectively exerted.

[0046] In addition, when a snow-melting agent such as calcium chloride is spread on the road surface to which the road surface freezing prevention method of this embodiment is applied, the snow-melting agent is easily retained on the road surface by the fine voids in the mortar layer. Therefore, the road surface freezing prevention method of this embodiment can improve the durability of the snow-melting agent's effect.

[0047] Due to the above-mentioned features, the method for suppressing road surface freezing in this embodiment can be suitably used on road surfaces in cold regions and other areas where road surfaces are prone to freezing in winter. EXAMPLES

[0048] The present invention will be described below with reference to more detailed examples, but the present invention is not limited to these examples.

[0049] <Comparative Example 1> The dense-graded asphalt mixture (13) was placed in a mold (formwork) heated to the compaction temperature, and then compacted (50 times on both sides) to obtain a specimen of the dense-graded asphalt mixture (13). This was used as the specimen for Comparative Example 1.

[0050] <Example 1> Sodium formate as a metal salt compound of an organic acid was added to water and mixed to prepare a freeze inhibitor with a sodium formate concentration of 20% by weight. Next, 23.0 parts by weight of an emulsion of an acrylic acid ester polymer as a polymer emulsion (aqueous dispersion of a polymer obtained by polymerizing an acrylic acid ester, polymer content as solids: 38% by weight, glass transition temperature (Tg): -52°C), 22 parts by weight of cement (ultrafast hardening cement) as a solidifying agent, and 55.0 parts by weight of fine aggregate (grain size 1.7 mm or less, proportion of fine aggregate with a grain size of 0.6 mm or less in the total amount of fine aggregate: 22% by weight) were mixed in a mixer and mixed to obtain mortar.

[0051] Next, the above-mentioned antifreeze agent was sprayed at 0.2 L / m onto the surface of a specimen of dense-graded asphalt mixture (13) obtained in the same manner as in Comparative Example 1. 2 That is, 40 g / m2 was sprayed on the surface of the test specimen. 2 After one hour had passed since the antifreeze agent was sprayed, the above mortar was applied to a thickness of about 1 mm on the surface of the specimen on which the antifreeze agent had been sprayed, forming a mortar layer. The specimen was then left to cure for two hours at room temperature to harden the mortar. This specimen was used as Example 1.

[0052] <Comparative Example 2> A mixture containing sodium formate was obtained in the same manner as the mortar in Example 1, except that sodium formate was further added as a metal salt compound of an organic acid. The obtained mixture was sprayed at 0.7 MPa using a lysine gun onto the surface of a specimen of dense-graded asphalt mixture (13) obtained in the same manner as in Comparative Example 1, and left at room temperature for 2 hours to form a film with a thickness of about 1 mm, which was used as the specimen for Comparative Example 2. The amount of sodium formate added when producing the mixture was 40 g / m2, so that the amount of sodium formate dispersed on the surface of the specimen when the mixture was made into a film with a thickness of about 1 mm. 2 The amount was set to be:

[0053] <Icing tension test> According to the "Method of measurement using a tensile tester to determine ice adhesion tensile strength" described in "Special Issue on Pavement Performance Evaluation Method" (Japan Road Association, March 2008), the antifreeze effect was evaluated indoors for the specimens of Example 1, Comparative Example 1, and Comparative Example 2. Figure 1 shows the ice adhesion tensile test method.

[0054] Specifically, the test temperature was set to -5°C, and a thin ice film was formed on the surface of the specimen 10. Next, the measurement jig 20 with the nonwoven fabric 30 attached was prepared, and the nonwoven fabric 30 attached to the measurement jig 20 was saturated with water and placed on the surface of the specimen 10. Next, the surface of the specimen 10 was subjected to a load of 4 kPa ground pressure, and the specimen was cured in an environment of -5°C for 4 hours. The load was then removed, and a rubber plate 40 was placed on the top of the measurement jig 20, and a steel ball weighing 420 g was dropped onto the surface from a height of 25 cm 10 times. After that, the measurement jig 20 was pulled out from the specimen 10, and the maximum load when the measurement jig 20 was pulled out was measured, and this was taken as the ice adhesion tensile strength. The smaller the ice adhesion tensile strength, the higher the freeze inhibition effect. In addition, in order to evaluate the durability of the freeze inhibition effect, the same specimen was repeatedly subjected to ice adhesion tensile tests. If the ice adhesion tensile strength does not increase significantly even after repeated tests, it can be determined that the freeze inhibition effect is highly durable. Alternatively, even if the ice adhesion tensile strength increases significantly as a result of repeated testing, the greater the number of tests at which the ice adhesion tensile strength increases significantly, the greater the durability of the anti-freezing effect can be judged. The measurement results are shown in Figure 2.

[0055] As shown in FIG. 2, the specimen of Example 1, which used sodium formate as the metal salt compound of an organic acid, had a significantly reduced freezing tensile strength compared to the specimen of the dense-graded asphalt mixture (13), and it can be said that this has an excellent anti-freezing effect.

[0056] <Evaluation of the durability of the effects of snow-melting agents> The surface of the specimen of Example 1 was exposed to running water for 2 days to allow sodium formate to flow out from the surface of the specimen. The specimen was subjected to the ice adhesion tensile test in the same manner as above. Next, an aqueous calcium chloride solution containing calcium chloride as a snow-melting agent was applied to the specimen so that the amount of calcium chloride on the surface of the specimen was 20 g / m 2 The surface of the specimen after the ice adhesion tensile test was sprayed with calcium chloride solution so that the ice adhesion tensile strength was increased. The ice adhesion tensile test was repeatedly performed on the specimen after the calcium chloride solution was sprayed. In the ice adhesion tensile test after the calcium chloride solution was sprayed, the greater the number of tests when the ice adhesion tensile strength increased significantly, the higher the durability of the effect of the snow-melting agent can be determined. The test specimen of Comparative Example 1 was also similarly evaluated for the durability of the effect of the snow-melting agent. The measurement results are shown in FIG. 3. In FIG. 3, the result of the first test represents the result after the surface of the specimen was exposed to running water for two days. In FIG. 3, the results of the second to sixth tests represent the results after the calcium chloride solution was sprayed on the surface of the specimen.

[0057] As shown in Figure 2, the specimen of Example 1 obtained by the method of spraying a freeze inhibitor containing a metal salt compound of an organic acid and applying a mortar containing a polymer emulsion, a solidifying agent, and an aggregate to form a mortar layer had a small freeze adhesion tensile strength and was excellent in freeze inhibition effect (particularly the first test result). Furthermore, even when the freeze adhesion tensile test was repeatedly performed on the specimen of Example 1, the freeze adhesion tensile strength did not increase significantly, and the freeze inhibition effect was also excellent in durability.

[0058] On the other hand, the specimens of Comparative Example 1, which was not sprayed with antifreeze agent, and Comparative Example 2, which was obtained by spraying a mixture containing a metal salt compound of an organic acid, a polymer emulsion, a solidifying agent, and an aggregate, had high ice adhesion tensile strength and poor antifreeze effect. Furthermore, in the specimens of Comparative Example 1 and Comparative Example 2, the ice adhesion tensile strength increased significantly when the ice adhesion tensile test was repeated, and the durability of the antifreeze effect was poor.

[0059] Furthermore, as shown in FIG. 3, even when the test specimen of Example 1 was repeatedly subjected to the ice adhesion tensile test after the sodium formate as the metal salt compound of an organic acid was drained out and the calcium chloride aqueous solution as the snow-melting agent was sprayed, the ice adhesion tensile strength did not increase significantly, which demonstrated that the effect of the snow-melting agent was excellent in durability.

Claims

1. A first step of spraying an antifreeze agent containing a metal salt compound of an organic acid onto a road surface; A method for suppressing freezing of a road surface, comprising a second step of applying mortar containing a polymer emulsion, a solidification material, and an aggregate to the road surface to form a mortar layer.

2. 2. The method for suppressing freezing of road surfaces according to claim 1, wherein the content of the metal salt compound of the organic acid in the antifreeze agent is 5 to 45% by weight.

3. In the first step, the amount of the antifreeze agent sprayed is 0.05 to 0.5 L / m 2 3. The method for suppressing freezing of road surfaces according to claim 1 or 2.

4. In the first step, the amount of the metal salt compound of the organic acid placed on the road surface by spraying the antifreeze agent is 2.5 to 225 g / m 2 3. The method for suppressing freezing of road surfaces according to claim 1 or 2.

5. A method for suppressing road surface freezing according to claim 1 or 2, wherein in the second step, the thickness of the mortar layer is 0.2 to 4 mm.

6. The method for suppressing freezing of road surfaces according to claim 1 or 2, wherein the second step is carried out 10 minutes to 2 hours after the first step.

7. 3. The method for suppressing freezing of road surfaces according to claim 1, wherein the metal salt compound of an organic acid is a metal salt of a carboxylic acid.

8. 8. The method for suppressing freezing of road surfaces according to claim 7, wherein the metal salt compound of an organic acid is a metal salt of formic acid.

9. 3. The method for suppressing freezing of road surfaces according to claim 1, wherein the polymer emulsion is an emulsion of an acrylic ester polymer.

Citation Information

Patent Citations

  • Freezing preventing paving method

    JP1987160302A

  • Construction method of asphalt group surface treatment material with freeze suppressing function

    JP1995324307A

  • Road surface pavement composition and road surface paving method

    JP2010222910A

  • Freezing suppression surface treatment mixture for road surfaces

    JP2020076210A

  • Repair material for civil engineering construction, and repairing method for civil engineering construction

    JP2021138582A